Research on Clinical Preventive Services for Adolescents and Young Adults: Where Are We and Where Do We Need to Go? - Harris, Sion K. (J Adolesc Health, 2016)
We reviewed research regarding system- and visit-level strategies to enhance clinical preventive service delivery and quality for adolescents and young adults. Despite professional consensus on recommended services for adolescents, a strong evidence base for services for young adults, and improved financial access to services with the Affordable Care Act’s provisions, receipt of preventive services remains suboptimal. Further research that builds off successful models of linking traditional and community clinics is needed to improve access to care for all youth. To optimize the clinical encounter, promising clinician-focused strategies to improve delivery of preventive services include screening and decision support tools, particularly when integrated into electronic medical record systems and supported by training and feedback. Although results have been mixed, interventions have moved beyond increasing service delivery to demonstrating behavior change. Research on emerging technology—such as gaming platforms, mobile phone applications, and wearable devices—suggests opportunities to expand clinicians’ reach; however, existing research is based on limited clinical settings and populations. Improved monitoring systems and further research are needed to examine preventive services facilitators and ensure that interventions are effective across the range of clinical settings where youth receive preventive care, across multiple populations, including young adults, and for more vulnerable populations with less access to quality care.